Over the range : a history of the Promontory Summit route of the Pacific railroad - Francaviglia, Richard V. (Utah State University Press, 2008)
Francaviglia looks anew at the geographical-historical context of the driving of the golden spike in May 1869. He gazes outward from the site of the transcontinental railroad's completion - the summit of a remote mountain range that extends south into the Great Salt Lake. The transportation corridor that for the first time linked America's coasts gave this distinctive region significance, but it anchored two centuries of human activity linked to the area's landscape. Francaviglia brings to that larger story a geographer's perspective on place and society, a railroad enthusiast's know.